سِکھ مَت کا فلسفہ عبادت اور اُن پر تعلیماتِ اسلامیہ کے اثرات (گُرو گَرنتھ صاحب کی روشنی میں): The philosophy of worship in Sikhism and the effects of Islamic teachings on them (In the light of Gurū Granth Ṣāḥib) - Ahmad, Sheraz (Al-Amīr Research Journal for Islamic Studies, 2021)
In Sikhism, the concept of worship revolves around remembrance of God and prayers to God Almighty. Various terms are used for worship in Sikhism among them are Naam Japna, Path Karna and Naam Simran. The best form of worship is to always meditate on the name of God and to sing the words of the Sikh Gurus in a humorous manner. This concept of worship in Sikhism has a limited meaning, while the comprehensive system of worship offered by Islam does not exist in Sikhism. However, inspired by Islamic teachings, prayers, remembrance of God, selection of words for worship from the Holy Book and the construction of places of worship in the Islamic style are arguments to accept the influence of Islam. Sikhism teaches to seek God’s pleasure through worship and to be freed from the cycle of reincarnation through good deeds and to worship the only true God.In this article a detailed study is presented regarding the philosophy of worship in Sikhism and impacts of Islamic teachings on them.